ANALYSIS OF WOMEN'S PARTICIPATION IN COMMUNITY EMPOWERMENT PROGRAMS IN THE COASTAL AREAS OF CIREBON CITY - Oktavia, Fitka Dwi; Alfirdaus, Laila Kholid; -, Wijayanto - (Journal of Politic and Government Studies, 2024)
This research investigates women's participation in coastal community empowerment programs in Cirebon City, focusing on social, economic, and cultural factors influencing their engagement. Through qualitative methods, particularly interviews, it uncovers the multifaceted challenges faced by coastal women and evaluates the effectiveness of empowerment initiatives. The findings reveal significant barriers, including social norms and financial constraints, hindering coastal women's economic and social involvement beyond domestic responsibilities. Despite government-sponsored efforts and stakeholder initiatives, persistent issues require further action. Government-led initiatives like P2WKSS, Sekoper Cinta, 100 KK Binaan, and Sekolah Keluarga Cirebon have facilitated women's empowerment, fostering skill development and greater social and economic participation. These endeavors aim to amplify women's contributions to inclusive and sustainable coastal development. The study underscores the pivotal role of women's participation in enhancing the wellbeing of coastal communities and fishing families. While some face obstacles like work commitments or lack of awareness, others actively engage in community health or educational programs. Supportive factors such as awareness, family backing, economic needs, and conducive environments bolster women's involvement in empowerment programs. This research highlights the significance of women's engagement in coastal empowerment initiatives for fostering inclusivity, reducing gender disparities, and offering contextually relevant solutions. Strategies like early socialization, deliberation, organization, and participatory review hold promise for enhancing women's involvement despite existing challenges. In conclusion, this research deepens understanding of gender dynamics in coastal community development by illuminating coastal women's lives and their participation in empowerment initiatives. It underscores the need for ongoing efforts to overcome barriers and foster an environment conducive to women's active engagement in coastal development endeavors